PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR - Ramadanti, Intan; Gumilar, Rendra; Srigustini, Astri (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The focus of this research is to find out the low learning outcomes of students in Economics subjects. The purpose of this study is to find out the improvement of student learning outcomes through the application of a make a match type cooperative learning model. Using the Quasi Experiment method with a quantitative approach. The population of this study is all students of class XI IPS SMAN 1 Cisayong as many as 96 students, the sampling technique uses the purposive sampling technique with an experimental class of 32 people using the Make a Match Type Cooperative Learning model and the control class of 32 people using a conventional model with the lecture method. The results of the study showed that there was an influence of using the make a macth type cooperative learning model on student learning outcomes on international trade policy material, where Ha was accepted if the sig value (2-tailed)< 0.005 and based on the research obtained a sig value. (2-tailed) of 0.000<0.005. The average score of the experimental class is higher than that of the control class, thus it can be concluded in this study that the make a match type cooperative learning model can improve student learning outcomes